1991
DOI: 10.1107/s0108768191002707
|View full text |Cite
|
Sign up to set email alerts
|

Linear Si–O–Si fragments: structure of 1,1,3,3-tetramethyl-1,3-bis[(2-oxo-1-pyrrolidinyl)methyl]disiloxane dihydrochloride and analysis of displacement parameters

Abstract: An X-ray diffraction study of 1,1,3,3-tetramethyl-1,3-bis[(2-oxo-l-pyrrolidinyl)methyl]disiloxane di-* To whom correspondence should be addressed.0108-7681/91/040544-05503.00hydrochloride, C14H30N203SizZ+.2C1 -, Mr=357

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The oxygen atom linking the siloxane units exhibits low Lewis basicity, which results in hydrophobic material properties, whereas the analogous oxygen atom in organic ethers (R 3 C‐O‐CR 3 ) is considerably more basic . The Si‐O‐Si angle in most siloxane compounds is between 140° and 180°, which is far higher than the tetrahedral angle of about 110° adopted by ethers . In previous studies, it has been shown that decreasing the Si‐O‐Si angle leads to a significant increase in the basicity of siloxanes .…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen atom linking the siloxane units exhibits low Lewis basicity, which results in hydrophobic material properties, whereas the analogous oxygen atom in organic ethers (R 3 C‐O‐CR 3 ) is considerably more basic . The Si‐O‐Si angle in most siloxane compounds is between 140° and 180°, which is far higher than the tetrahedral angle of about 110° adopted by ethers . In previous studies, it has been shown that decreasing the Si‐O‐Si angle leads to a significant increase in the basicity of siloxanes .…”
Section: Introductionmentioning
confidence: 99%